Kajian Terhadap Unsur Kalimat Subjek, Objek, Predikat, dan Keterangan - Jajang Setiawan; Retno Setya Budiasningrum; Ali Satri Efendi (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to examine the elements in a sentence, various basic patterns that form a sentence and identify basic patterns in a sentence. The method used in this study is descriptive analysis with a qualitative approach. The results of the study indicate that the subject, predicate, object, and description are elements of a sentence that are basic components in forming a coherent and meaningful syntactic structure. The subject performs the action or the main topic of discussion, the predicate as an explanation of the action or condition, the object as the recipient of the action or condition, and the adverb as a complement that provides additional information. All elements play a crucial role in forming clear and precise sentences.